Kewirausahaan Digital di Era Industri 5.0: Sinergi Manusia dan Teknologi dalam Membangun Ekonomi Berkelanjutan - Andalangi Maatuil, Rexy; Ferdinandus Ijie; Aprilio Killis; Septian Latjube (Indonesia Economic Journal, 2025)
The era of Industry 5.0 marks a paradigm shift from full automation toward a harmonious collaboration between humans and technology. This study aims to analyze the role of digital entrepreneurship as a key instrument in building a sustainable economy through the synergy of human intelligence and technological innovation. Using a qualitative literature review approach with descriptive analytical methods, this research explores recent academic findings on digital innovation, sustainability, and inclusive economic development. The results indicate that digital entrepreneurship not only stimulates economic growth but also integrates human values, ethics, and social responsibility into business practices. Industry 5.0 emphasizes human-centered innovation, in which technology serves as a collaborative partner that enhances creativity, efficiency, and social impact. Sustainable digital entrepreneurship bridges economic inequality, generates new employment opportunities, and strengthens national competitiveness. The study recommends strengthening digital literacy, developing inclusive innovation ecosystems, and implementing technological ethics as strategic pathways toward a fair and sustainable digital economy.